2021
DOI: 10.3390/ijerph182111490
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Exposure through Different Drinking Water Sources in a Contaminated Basin in Guanajuato, Mexico: A Deterministic Human Health Risk Assessment

Abstract: Water fluoride levels above the World Health Organization’s guideline (1.5 mg/L), common in overexploited aquifers, represent a health hazard. Our objective was to assess the health risks posed by exposure to fluoride in different drinking water sources in a contaminated basin in Mexico. Fluoride was measured in mutual drinking water sources and in the urine of 39 children and women. Risks were estimated through hazard quotient (HQ) by drinking water source. Dental fluorosis was assessed in the children. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
8
0
1
Order By: Relevance
“…The natural recharge in the scenarios analyzed is similar and converges at a value of 219 × 10 6 m 3 /a ± 8 × 10 6 (7 ± 0.25 m 3 /sec), which contrasts with the extraction volume estimated in 2020 at 1000 × 10 6 m 3 /a (32 m 3 /sec), which is over four times higher. This situation explains (i) many of the negative impacts reported in the basin over the past two decades [2,[51][52][53] due to the lowering of the water table by 2-10 m/a caused by the concentration of pumping (Figure 3); (ii) the progressive temperature increase of water in the wells; and (iii) the occurrence and progressive increase of chemical elements that are harmful to health and the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural recharge in the scenarios analyzed is similar and converges at a value of 219 × 10 6 m 3 /a ± 8 × 10 6 (7 ± 0.25 m 3 /sec), which contrasts with the extraction volume estimated in 2020 at 1000 × 10 6 m 3 /a (32 m 3 /sec), which is over four times higher. This situation explains (i) many of the negative impacts reported in the basin over the past two decades [2,[51][52][53] due to the lowering of the water table by 2-10 m/a caused by the concentration of pumping (Figure 3); (ii) the progressive temperature increase of water in the wells; and (iii) the occurrence and progressive increase of chemical elements that are harmful to health and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative health impact on children was carried out in 2003. The quantitative impact of fluoride in drinking water has been studied in the basin [51,52]. In fact, an extension of the National University ENES-León opened in 2011 to train professionals in odontology, agronomical administration, and physiotherapy to attend to some aspects of these problems, but the programs offered do not include hydrogeology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conducted a multiple analysis to estimate the impact of the effect of the combination of various fluoride sources and demographic variables and obtained a multiple association model with statistical significance, where we tested the interactions between the dose of water intake, involuntary toothpaste intake, amount of table salt intake, fluoride urinary excretion and sex of the participants. We found that the variable sex influenced the model from the category of boy or girl, indicating that boys probably ingested greater amounts of water or Table salt than girls, due to greater muscle mass that consequently increases the intake needs ( 53 ). Likewise, the strength of association of urinary fluoride excretion was increased in multiple analysis, probably due to the strong positive correlation with the water ingestion exposure dose, showing a higher urinary fluoride concentration in children with high levels of water ingestion fluoride exposure dose.…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence to suggest a potential dysregulated metabolism induced by fluoride that differed by sex in pre-pubertal children. In Mexico, fluoride exposure primarily originates from fluoridation in salt ( Cantoral et al, 2019 ), followed by naturally occurring drinking-water fluoride exposure ( Armienta and Segovia, 2008 ; Farías et al, 2021 ). Greater consumption of fluoride-based diets or salty foods in boys at later ages could explain higher fluoride levels in this population and subsequent altered metabolism as evidenced by a higher level of fluoride estimated in boys than girls across all ages and media.…”
Section: Discussionmentioning
confidence: 99%
“…While fluoride is present in dental products, it is commonly found in fluoridated municipal drinking water, at trace levels in natural water sources, as well as in food and beverages. In Mexico, while municipal water is not fluoridated, there is wide availability of naturally occurring fluoride in drinking water ( Armienta and Segovia, 2008 ; Farías et al, 2021 ), and exposure via foods containing elevated levels of fluoridated salt ( Cantoral et al, 2019 ). More specifically, salt fluoridation is required in Mexican municipalities when naturally occurring fluoride does not exceed certain limits (0.7 ppm) ( Secretaría de Salud, 1994 ; Gobierno de México, 2023 ).…”
Section: Introductionmentioning
confidence: 99%